Altered effective connectivity from the posterior insula to the amygdala mediates the relationship between psychopathic traits and endorsement of the Harm foundation. (6th June 2022) - Ye, Shuer; Li, Wei; Zhu, Bing; Lv, Yating; Yang, Qun; Krueger, Frank
Abstract: Psychopathic traits have been demonstrated to be associated with different moral foundations. However, the neuropsychological mechanism underlying the relationship between psychopathic traits and moral foundations remains obscure. Our study examined the effective connectivity (EC) of psychopathy-related brain regions and its association with endorsement to moral foundations (Harm, Fairness, Loyalty, Authority, and Purity)—combining questionnaire measures, resting-state fMRI (RS-fMRI), and Granger causality analysis. We administered the Levenson Self-Report Psychopathy Scale and Moral Foundation Questionnaire to 78 college students after RS-fMRI scanning. Our results showed that total and primary psychopathy negatively predicted endorsement of the Harm foundation. The EC from the posterior insula to the amygdala was negatively associated with primary psychopathy but positively associated with endorsement of the Harm foundation. Altered posterior insula-amygdala EC partially mediated the relationship between primary psychopathy and endorsement of the Harm foundation. Our findings demonstrated that individuals with elevated psychopathic traits may have atypical processes in recognizing and integrating bodily state information into emotional responses —leading to less concern for harm-related morality. Our findings deepen the understanding of the neuropsychological mechanism underlying the relationship between psychopathic traits and morality, providing potential neurobiological explanations for increased moral transgressions, especially those harm-related transgressions, committed by psychopathic individuals.